Numerical simulation of the stress field in California: implications for the stress perturbation by Big Bend and Garlock Fault - Prasad Koirala, M.; Hayashi, D. (TRABAJOS DE GEOLOGÍA, 2010)
2D finite element modelling is used to analyze the state of stress in and around the SanAndreas Fault System (SAFS) taking the whole area of California. In this study we focus on the stateof stress at the general seismogenic depth of 12 km, imposing elastic rheology. The purpose of the presentstudy is to simulate the regional stress field and also to find the stress perturbation due to Big Bendand Garlock Fault. Although in nature there is lateral and vertical variation in rheology, our highly simplifieddomain properties have simulated results comparable with the observed data. Our imposedboundary condition (fixed North American plate, Pacific plate motion along N34W vector up tonorthern terminus of the San Andreas faults and N50E vector motion for the subducting Gorda plate)simulated the present day regional Hmax orientation and velocity vector. Simulated results show localeffect on the stress field and displacement vector by the Big Bend and is further enhanced by theGarlock Fault, which may have significant impact on fault slip, stress, and hence deformation in thesurrounding region.